Chlorophyll-a mapping from the moderate resolution imaging spectroradiometer data in the South China Sea - Kueh, Hsiao Chin (2005)
The amount of chlorophyll-a depends on the amount of algae and can also be used as an indicator of phytoplankton abundance and biomass in coastal water. The concentration of chlorophyll-a also could be a general measure of water quality. A series of Moderate Resolution Imaging Spectroradiometer (MODIS) data acquired on different dates were used in this study since chlorophyll-a concentration change over time. In this study, four different algorithms had been chosen to extract chlorophyll-a concentration from MODIS data in the South China Sea. MODIS data acquired on 13 Jun 2001 was used to derive the coefficients in the algorithm since ground truth data is available. The accuracy of these algorithms was also assessed by comparing the correlation between measured and calculated chlorophyll-a values. The best algorithm is the Gordon algorithm with a R2 value of 0.735. Thus, Gordon’s algorithm was used to obtain chlorophyll-a distribution during the north east monsoon and south west monsoon period in 2003 and 2004. The results show that during the north east monsoon and south west monsoon periods, the chlorophyll-a concentration is between 0.1-0.5 mg m-3 while the chlorophyll-a concentration during the inter-monsoon period is between 0.1-1.0 mg m-3.